2022
DOI: 10.3390/life12101664
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Vitamin D in Kidney Transplantation Outcomes: A Systematic Review

Abstract: The aim of this systematic review is to assess the impact of vitamin D on the outcomes of kidney transplantation and investigate whether its deficiency is associated with a negative impact. Methods: We conducted a systematic literature search in PubMed, Scopus and Cochrane databases, as well as gray literature. Ultimately, 16 articles with an average of 255.75 patients were included in this review. These articles compared the long-term outcomes of vitamin D deficiency and/or vitamin D supplementation therapy o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 41 publications
0
5
0
1
Order By: Relevance
“…This study is the first, to our knowledge, to show an association between the 25(OH)D status post‐KT and dn DSAs occurrence 32 . Moreover, this study presents an original longitudinal assessment of 25(OH)D levels up to 3 years post‐transplant.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations
“…This study is the first, to our knowledge, to show an association between the 25(OH)D status post‐KT and dn DSAs occurrence 32 . Moreover, this study presents an original longitudinal assessment of 25(OH)D levels up to 3 years post‐transplant.…”
Section: Discussionmentioning
confidence: 86%
“…One strength of this study is the yearly longitudinal measurement of 25(OH)D levels for 36 months for a high number of KTRs 32 . Indeed, previous studies merely provided a single 25(OH)D measurement after KT 7–10,12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the studies showed a negative effect of vitamin D deficiency on kidney transplantation by being associated with a worse graft function, higher incidence of acute rejection episodes, higher incidence of proteinuria and lower overall graft and patient survival rate ( 1 ).It is well-established that Vitamin D (VD) plays a crucial role in mineral and bone metabolism as well as the treatment of secondary hyperparathyroidism in patients with chronic kidney diseases (CKD). Recently, there has been an increasing focus on the immunomodulatory effects of VD in KTRs.…”
Section: Introductionmentioning
confidence: 99%